Peran Kepala Sekolah Dalam Meningkatkan Mutu Dan Kinerja Guru Sekolah Dasar - Zuliyanti, T.Rika; Zaka Hadikusuma Ramadan (Jurnal Elementaria Edukasia, 2023)
The role of the principal in improving the quality and performance of teachers is very important, the quality and quality of teachers has a major influence on student development. Good teacher quality and performance will shape the quality of education in schools. Qualified graduates are influenced by the quality and performance of teaching staff, the birth of high achieving and qualified graduates depends on the quality and performance of educational staff in an institution. This study aims to describe the role of the principal in improving the quality and performance of teachers at SDN 16 Tanjung Peranap, this type of research is qualitative. This research was conducted at an elementary school in Tebing Tinggi District, Meranti Regency with the subject of the school principal and teacher. Methods of data collection using observation, interviews and documentation. Data analysis is a qualitative analysis. The results of this study indicate that the role of the principal in improving teacher quality and performance is very important because the principal is a leader and role model in the school environment, so it is very important for the principal to fulfill and carry out his role. in improving quality and performance as much as possible, where the principal acts as: Educator, Manager, Administrator, Innovator, Motivator, Supervisor and Leader.